Philosophical Foundations of the Transformation of the Judicial Method of Rights Protection in the Context of the Creation of a Unified Information Space of the EEU - Rusakova, Ekaterina P.; Frolova, Evgenia E. (Տիգրան Մեծ)
The article is devoted to the study of the dispute resolution procedure by the EAEU Court in the context of creating a single information space of the member countries of this integration association. Within the framework of the theoretical and practical orientation of this study, special attention is paid to conceptual problems related to the description of key social and digital phenomena that arise in the process of implementing the digital agenda and its impact on the judicial method of protecting the rights and legitimate interests of citizens and business entities. The transition to digital or electronic justice will increase the efficiency of the EAEU Court and create the most attractive conditions for the parties to the dispute to protect their rights and legitimate interests. Digitalization provides for large-scale changes in the field of justice, the emergence of new means of proof, the introduction of an electronic form of cases, remote court sessions all this leads to a change in the fundamental principles of legal proceedings. The solution to this problem should begin with the creation of a comprehensive program of legislative changes to the judicial method of protecting rights related to their digital transformation within the EAEU.
Keywords: Philosophy of low